Star Wars episode 1 visual dictionary - Reynolds, David West (Dorling Kindersley London, 1999)
Text and illustrations present characters from episode I of "Star Wars" and the technology they use, including Qui-Gon Jinn and his wrist hologram projector, the space freighters of the Nemoidians, and the lightsabers of the Jedi Knights. Amazing annotated photography gives an unrivaled insight into the characters, costumes, droids and gadgetry of Star Wars: Episode I